'A little whisper in the ear': how developing relationships between pupils with attachment difficulties and key adults can improve the former's social, emotional and behavioural skills and support inclusion. Issue 4 (2nd October 2021) - Wall, Sarah
ABSTRACT: Children with attachment difficulties can experience barriers to learning and their externalising and internalising behaviours can challenge staff: ultimately, such encounters may result in exclusion from school. This paper examines how settings can support the inclusion of pupils with attachment difficulties, through employing a specific member of staff who is not the teacher (1:1), as an additional attachment figure; hereafter, termed a key adult. Using mixed methods, my multiple-case study applies attachment, and secure base, theories to the educational context and evaluates the impact and efficacy of developing supportive relationships with two at-risk children (Child A and B). The findings suggest that key adults can support areas of social, emotional, and behavioural skills previously believed impervious to change. Furthermore, such individuals enable pupils with attachment difficulties to attain equal opportunities and safeguard against exclusion.